Mobilising the food system concept: Unpacking debates and applications - Maye, Damian; Helliwell, Richard; Morris, Carol (The International Journal of Sociology of Agriculture and Food, 2025)
The food system concept has become the ‘go-to’ framework to galvanise discussion and bring together academics, policymakers and industry stakeholders to debate changes needed in how our food is grown, made, sold, eaten and governed. The concept is not new, but the paper shows a resurgence in application across science and social science in recent years. What is lacking, however, is more critical analysis as to why this concept is increasingly mobilised and what it offers agri-food scholarship going forward. Inspired by Jackson et al’s (2006) analysis of the food commodity chain as ‘chaotic concept’, this paper undertakes a critical review of the peer-reviewed, English language literature on food system(s) nationally in the UK and internationally. The analysis begins with a review of food system scholarship to explain concept origins and key features of systems thinking. The second part examines uptake in the wider literature. This spans 1987-2024 and reviews trends from Scopus and Web of Knowledge, followed by a structured review of social science articles for two case studies concerning respectively ‘food system transformation and crisis’ (process-based) and ‘food system and the urban’ (place-based). The analysis reveals a pattern of bi-polarisation: the first mobilises the food system as a heurist framing in contrast to the second more systemic framing. The former dominates the material reviewed. The paper argues that recognising not only different mobilisations but also the dominance of heuristic food system uses is important, given its prominence to support changes in the governance and politics of food.